It Takes an E-Village: Supporting African American Mothers in Sustaining Breastfeeding Through Facebook Communities. (August 2019) - Robinson, Ayanna; Davis, Marsha; Hall, Jori; Lauckner, Carolyn; Anderson, Alex Kojo
Background: Lack of breastfeeding support is a common barrier reported by African American mothers, whose breastfeeding rates remain significantly below the national average. Despite mothers' reported use of social network sites to access support on topics relating to child rearing, few studies have examined their use to exchange breastfeeding support. Research aims: To describe (1) the experiences of African American mothers who participate in breastfeeding support groups on Facebook and (2) the breastfeeding beliefs, practices, and outcomes for this population of mothers. Methods: This was a prospective, cross-sectional qualitative study with an online focus group design. The study was guided by Black Feminist Thought and an integrated model of behavior prediction. Four online focus groups ( N = 22) were conducted using video conferencing during September 2017 with African American mothers who were participating in breastfeeding support groups on Facebook. Results: Thematic analysis was used to develop four themes and two subthemes, including creating a community for Black mothers, online interactions and levels of engagement, advantages of participating in online support groups, critiques of online support groups, empowerment of self and others, and shifts in breastfeeding perceptions and decisions. Among participants in this study, positive imagery of African American breastfeeding mothers and ongoing support from women with shared experiences improved confidence with public breastfeeding and prolonged goals for breastfeeding duration. Conclusion: Receiving peer support within Facebook communities may positively influence breastfeeding norms and confidence in breastfeeding, help mothers to overcome breastfeeding challenges, and ultimately extend intended breastfeeding duration.